IMPROVING ENGLISH VOCABULARY MASTERY THROUGH WORD GAME - Lube, Chrissandra Intan; Nuraeni, Siti (IKIP Siliwangi, 2020)
Vocabulary is very important in learning English. To master four skills in English, we need mastery vocabulary first. So, the researchers use word game in the classroom to make students interest to learn vocabulary. The objective of this research is to know that the word game is effective to improve students’ vocabulary or not, through word game strategy among seventh-grade students of SMP Muslimin Cililin in the academic year of 2018/2019. The method used in this research is quantitative technique and the pre-experimental as a research design. This research was conducted in one class. The population in this research is seventh-grade students of SMP Muslimin Cililin with the total number of the population are 273 students consisting of 7 classes, and the sample is class VII.C that consist of 30 students. The data were collected with the pretest and posttest as an instrument. The researchers conducted the tests before (pre-test) and after (post-test). After that the researchers gave students treatments consists of five meetings. The result showed that Sig. 0.000 and it was lower than 0.005 so, the null hypothesis was rejected and the alternative hypothesis was accepted. It means that teaching English vocabulary using a word game was effective to improve students’ vocabulary at seventh-grade. Keywords: Word game, students’ vocabulary mastery.